CMOS integrated oscillator - Long, Nicholas Jianming (2014)
In digital or analog circuits, the need to provide a stable operating frequency is extremely important. It is also not a simple feat to achieve such a stable frequency due to factors such as power supply and temperature which will affect the frequency provided.